Clinical and molecular features of patients with prefibrotic primary myelofibrosis previously diagnosed as having essential thrombocythemia in Japan. (25th April 2019) - Edahiro, Yoko; Araki, Marito; Inano, Tadaaki; Ito, Masafumi; Morishita, Soji; Misawa, Kyohei; Fukuda, Yasutaka; Imai, Misa; Ohsaka, Akimichi; Komatsu, Norio
Abstract: Objective: Prefibrotic/early primary myelofibrosis (pre‐PMF) and essential thrombocythemia (ET) exhibited different features of bone marrow; however, this is not always easy to judge objectively, making pathologists' distinction often suboptimal. In the WHO 2008 criteria, pre‐PMF was not defined as a subgroup of PMF; therefore, affected patients were at a higher risk of misdiagnosis with ET. In this study, we examined the prevalence of pre‐PMF patients among those previously diagnosed with ET in Japan. Method: We reviewed bone marrow specimens and clinical and molecular parameters of patients who were previously diagnosed with ET by the WHO 2008 criteria. Results: Among 107 ET patients, 13 patients were redefined as having pre‐PMF. Pre‐PMF patients exhibited a higher frequency of MPL mutation and increased platelet counts compared to true ET patients. Molecular analysis revealed the frequencies of high‐risk molecular mutations, such as ASXL1, EZH2, and SRSF2, were significantly increased in pre‐PMF patients than those in true ET patients. Conclusion: These results demonstrated the value of reexamining clinical records for patients diagnosed with ET by the WHO 2008 criteria and emphasized that adequate examinations of patients' bone marrow are crucial for an accurate diagnosis of pre‐PMF and ET.